Productive Language Skills Self-Efficiency for Foreign Students Learning Turkish: A Validity and Reliability Study - Sevim, Oğuzhan; Varışoğlu, Behice (Fırat University, 2023)
The aim of this study is to develop a reliable and valid scale that aims to measure the proficiency perceptions of Turkish language learners regarding productive language skills. In this scale development study, exploratory sequential design, which is one of the mixed research designs, was used. The participants of the research consisted of 224 foreign undergraduate students studying at TÖMERs affiliated to Atatürk and Gaziosmanpaşa universities between the academic years of 2020-2021. The Lawshe technique was used to determine the content validity of the scale items. The data obtained as a result of the scale application were analyzed in SPSS 18.0 and LISREL 8.4 programs. While examining the construct validity of the scale, exploratory factor analysis technique was used. After it was decided by exploratory factor analysis that the scale consisting of 26 items had a single factor structure, confirmatory factor analysis technique was also used to confirm this structure. According to the exploratory factor analysis findings, it was decided that the scale developed based on both the explained total variance values and the line graph values has a single factor structure. When the fit indices obtained as a result of confirmatory factor analysis were examined, it was determined that all fit indices showed acceptable fit. As a result of the reliability test, the Cronbach Alpha value was calculated to be 0.93; It has been determined that this value being at an acceptable level indicates that the internal consistency value of the scale is high. At the end of the study, a reliable and valid single factor scale consisting of 26 items was reached.

Türkçeyi yabancı dil olarak öğrenen yetişkin bireylerin üretici dil becerilerine ilişkin öz yeterlilik algılarını ölçmede kullanılacak güvenilir ve geçerli bir ölçek geliştirmek bu çalışmanın temel amacıdır. Çalışmada keşfedici sıralı desen kullanılmıştır. Araştırmanın katılımcıları; 2020-2021 eğitim-öğretim yılında Atatürk ve Tokat Gaziosmanpaşa üniversitelerinin Türkçe öğretimi merkezlerinde öğrenim gören 224 yabancı uyruklu lisans ve ön lisans düzeyindeki öğrencilerden oluşmaktadır. Ölçek maddelerinin kapsam geçerliğinin belirlenmesinde Lawshe tekniğinden yararlanılmıştır. Ölçek maddelerinin uygulaması sonucu elde edilen veriler SPSS 18.0 ve LISREL 8.4 programlarında çözümlenmiştir. Ölçeğin yapı geçerliği açımlayıcı faktör analizi tekniği ile yapılmıştır. Açımlayıcı faktör analizi sonuçları ölçeğin 26 maddeden oluşan tek faktörlü bir yapıya sahip olduğunu göstermiştir. Bu aşamadan sonra ortaya çıkan tek boyutlu yapıyı teyit etmek amacıyla doğrulayıcı faktör analizi tekniği de kullanılmıştır. Doğrulayıcı faktör analizi sonucunda elde edilen uyum indekslerinin kabul edilebilir uyumu gösterdiği belirlenmiştir. Yapılan güvenirlik testi sonucunda ise Cronbach Alfa değerinin 0.93 olduğu hesaplanmış ve ölçeğin iç tutarlılık değerinin yüksek olduğu tespit edilmiştir. Araştırmanın sonunda 26 maddeden oluşan tek faktörlü, güvenilir ve geçerli bir ölçeğe ulaşılmıştır.
TÜRKÇE ÖĞRENEN YABANCI ÖĞRENCİLER İÇİN ÜRETİCİ DİL BECERİSİ ÖZ YETERLİLİK ÖLÇEĞİ: GEÇERLİK VE GÜVENİRLİK ÇALIŞMASI